Register-based data of psychosocial working conditions and occupational groups as predictors of disability pension due to musculoskeletal diagnoses: a prospective cohort study of 24 543 Swedish twins - Ropponen, Annina (BioMed Central, 2013)
BACKGROUND: Occupations and psychosocial working conditions have rarely been investigated as predictors of disability pension in population-based samples. This study investigated how occupational groups and psychosocial working conditions are associated with future disability pension due to musculoskeletal diagnoses, accounting for familial factors in the associations. METHODS: A sample of 24 543 same-sex Swedish twin individuals was followed from 1993 to 2008 using nationwide registries. Baseline data on occupations were categorized into eight sector-defined occupational groups. These were further used to reflect psychosocial working conditions by applying the job strain scores of a Job Exposure Matrix. Cox proportional hazard ratios (HR) were estimated. RESULTS: During the 12-year (average) follow-up, 7% of the sample was granted disability pension due to musculoskeletal diagnoses. Workers in health care and social work; agriculture, forestry and fishing; transportation; production and mining; and the service and military work sectors were two to three times more likely to receive a disability pension than those in the administration and management sector. Each single unit decrease in job demands and each single unit increase in job control and social support significantly predicted disability pension. Individuals with high work strain or an active job had a lower hazard ratio of disability pension, whereas a passive job predicted a significantly higher hazard ratio. Accounting for familial confounding did not alter these results. CONCLUSION: Occupational groups and psychosocial working conditions seem to be independent of familial confounding, and hence represent risk factors for disability pension due to musculoskeletal diagnoses. This means that preventive measures in these sector-defined occupational groups and specific psychosocial working conditions might prevent disability pension due to musculoskeletal diagnoses.